PROFIL ADAPTABILITAS KARIR PESERTA DIDIK BERDASARKAN FAKTOR DEMOGRAFIS : Studi Deskriptif terhadap Peserta Didik Kelas IX SMP Negeri 14 Tasikmalaya Tahun Ajaran 2017/2018 - Rifki Pradinavika, - (2017)
Career adaptability is important for adolescent to achieve the developmental task of choosing and preparing a career. Junior high school students, who are involved in the adolescent development phase are faced with the first career selection which is selecting higher education institution. This study aims to obtain the description of career adaptability of class IX students of JHS 14 Tasikmalaya Academic Year 2017/2018 and the description of career adaptability of students based on genders, parents educational attainment, and family economic condition. The research was done by using quantitative approach and descriptive method. The tool to measure data was scale-shaped questionnaires adopted from Career Adapt-Abilities Scale (CAAS) developed by Savickas and Porfeli (2012). Population and sample of the research were 426 IX students of JHS 14 Tasikmalaya academic year 2017/2018. The results showed: (1) in general, adaptability of career of class IX students of JHS 14 Tasikmalaya academic year 2017/2018 is in adaptive category, (2) the career adaptability of students based on demographic factors (genders, parents educational level, and family economic situation) does not affect career adaptability. Recommendations for school counselor of JHS 14 Tasikmalaya that is to be able to design the basic career guidance services strategy to facilitate students in improving the ability of career adaptability.---- Adaptabilitas karir penting dimiliki remaja untuk mencapai tugas perkembangan memilih dan mempersiapkan karir. Peserta didik SMP termasuk dalam fase perkembangan remaja dihadapkan dalam pemilihan karir pertama yaitu pemilihan sekolah lanjutan. Penelitian ini bertujuan untuk memperoleh deskripsi adaptabilitas karir peserta didik kelas IX SMP Negeri 14 Tasikmalaya Tahun Ajaran 2017/2018, deskripsi adaptabilitas karir peserta didik berdasarkan gender, deskripsi adaptabilitas karir berdasarkan tingkat pendidikan orang tua, dan deskripsi adaptabilitas karir peserta didik berdasarkan keadaan ekonomi keluarga. Penelitian dilakukan dengan menggunakan pendekatan kuantitatif dan metode deskriptif. Alat pengukuran data menggunakan kuesioner berbentuk skala diadopsi dari Career Adapt-Abilities Scale (CAAS) yang dikembangkan oleh Savickas dan Porfeli (2012). Populasi dan sampel penelitian adalah peserta didik kelas IX SMP Negeri 14 Tasikmalaya tahun ajaran 2017/2018 yang berjumlah 426 orang. Hasil penelitian menunjukkan: (1) secara umum adaptabilitas karir peserta didik kelas IX SMP Negeri 14 Tasikmalaya tahun ajaran 2017/2018 berada pada kategori adaptif, (2) adaptabilitas karir peserta didik berdasarkan faktor demografis (gender, tingkat pendidikan orang tua, dan keadaan ekonomi keluarga) tidak mempengaruhi adaptabilitas karir. Rekomendasi bagi guru BK SMP Negeri 14 Tasikmalaya yaitu dapat merancang strategi layanan dasar bimbingan karir untuk memfasilitas peserta didik dalam meningkatkan kemampuan adaptabilitas karir peserta didik.